2021
DOI: 10.3390/antiox10060876
|View full text |Cite
|
Sign up to set email alerts
|

Amaranthus hypochondriacus L. as a Sustainable Source of Nutrients and Bioactive Compounds for Animal Feeding

Abstract: With the aim to explore the use of A. hypochondriacus seeds for animal feeding, the agronomic traits, nutrients, and bioactive compounds of four accessions with different origin (India, Nebraska, Iowa, and Pennsylvania) grown in a Mediterranean environment were studied. Proximate composition was determined using the official methods of analyses, fatty acid profile by gas chromatography, total phenolic content (TPC) and the scavenging activity (DPPH• and ABTS•+) by colorimetric method. A one-way ANOVA model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 62 publications
7
13
1
Order By: Relevance
“…According to Christie [ 24 ], each sample was turned into methyl esters by direct transesterification. The fatty acids profile was determined using a gas chromatographic system (Focus GC: Thermo Electron Corporation, Waltham, MA, USA) with a flame ionization detector (FID) for methyl esters [ 25 ]. An external standard mixture (Larodan Fine Chemicals: AB, Limhamnsgardens, Malmo, Sweden) was used to quantify each fatty acid amount.…”
Section: Methodsmentioning
confidence: 99%
“…According to Christie [ 24 ], each sample was turned into methyl esters by direct transesterification. The fatty acids profile was determined using a gas chromatographic system (Focus GC: Thermo Electron Corporation, Waltham, MA, USA) with a flame ionization detector (FID) for methyl esters [ 25 ]. An external standard mixture (Larodan Fine Chemicals: AB, Limhamnsgardens, Malmo, Sweden) was used to quantify each fatty acid amount.…”
Section: Methodsmentioning
confidence: 99%
“…Total fat was previously extracted ( 10 ) from each sample and subsequently turned into methyl esters (FAMEs) by direct transesterification ( 11 ) to analyze fatty acid profiles. FAMEs were dissolved in n-hexane, filtered, and injected into a gas chromatographic system (Focus GC, Thermo Electron Corporation, Waltham, Massachusetts, USA) with a flame ionization detector (FID) for FAME assessment according to Oteri et al ( 12 ). Fatty acid peaks were identified and quantified by comparison with an external standard composed of pure FAME mixture (Larodan Fine Chemicals, AB, Limhamnsgardens Malmo, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…The weights obtained in this study (based on 100 seeds per sample) were similar to those reported by De Bock et al in 2021 [ 19 ]. Other authors have reported highly variable values, ranging from 0.03 to 0.79 g, including species such as Amaranthus hypochondriacus [ 20 , 21 , 22 ]. However, in the present study, 6–32% higher seed weight was noted for MX1 and PU compared to the other three samples, which is consistent with their larger seed sizes.…”
Section: Discussionmentioning
confidence: 99%